A Gestão de água no Estado do Ceará, a teoria e a prática: o caso do Açude Pirabibu na Bacia do Banabuiu - Vasconcelos, Antonio Marcelo Bezerra (2013)
Urban growth is a Brazilian reality and has contributed to a lack of environmental preservation and water bodies in the state of Ceará. The case of the weir Pirabibu belonging to Sub-River Basin Banabuiú, distant 26 Km from the center of Quixeramobim, the process of environmental degradation emerged through human actions. Deforestation, fires and degradation of native forests began with an attempt at an occupancy of permanent preservation area, especially for use in moist areas of the reservoir. With these occupations used up, making deforestation, raise animals in hydraulic basin beyond the tract on fishing, often done on the banks of the dam. In this sub-basin are thirteen municipalities and Pirabibu weir located in the District of Damian Carneiro, belonging to the municipality of Quixeramobim. The environmental damage in the region of the dam Pirabibu, among other problems, may impair the quality of water that has the priority use, human supply. This work is the systematization of information on the occupation of the area of permanent protection, the use of ebb and major interventions by the committee and the management of the basin taken by the managing agency, in light of existing state law, to contribute to an integrated and participation of the various uses sustainably to be deployed. For the feasibility of the study was a literature review and information gathering with the governing body, with actors involved in water system Pirabibu and members of the respective committee. It is suggested to minimize the impacts, a search for policies and projects that enable the sustainable use, respecting and valuing empirical knowledge existing natural aspects, avoiding the occupation of APP, recovering riparian vegetation and preserving existing vegetation upstream of the weir. It is essential, in the interests of government, the best use of financial resources, as well as a management plan for the reservoir with an effective participation of the social actors involved